Application of Human Resource Management Strategy in Efforts to Increase Sales Turnover - Yoga Friyadi (Clean and Sustainable Production, 2023)
This research aims to identify and analyze the implementation of human resource management strategies in increasing the sales turnover of CV. Andika Jaya. This study is a descriptive qualitative research that used interviews with managers and employees as a data collection source, and the data analysis technique employed was the interactive model data analysis technique, which includes data reduction, data display, and conclusion drawing. The results of this study indicate that the human resource management strategies implemented by the company are the utilizer strategy, accumulator strategy, and facilitator strategy. The implementation of these strategies includes the utilizer strategy covering human resource (HR) planning, recruitment, and selection; the accumulator strategy includes training and development, career planning; and the facilitator strategy includes performance appraisal and compensation, which have been well executed. Based on the analysis results, it can be concluded that the human resource management strategies applied are capable of increasing the company's sales turnover.